Unintended consequences of selling B2B digital subscription add-ons for customer onboarding - Lena Steinhoff; Jisu J. Kim; Vamsi K. Kanuri; Robert W. Palmatier (Journal of the Academy of Marketing Science, 2025)
Business-to-business (B2B) software-as-a-service (SaaS) providers increasingly bundle add-on services with their core service. The implications of such bundles for onboarding customers to the relationship remain unclear; in particular, the common practice of trying to maximize add-on bundling during the customer acquisition phase arguably might conflict with goals to achieve long-term retention of customers. The current study therefore focuses explicitly on the impact of add-on bundling on customer retention during the onboarding stage, using multiple methods. A theories-in-use exploration suggests that the positive effects of add-on bundling may not manifest in the initial relational stage of customer onboarding. A field study involving a B2B SaaS provider further reveals that bundling more add-on services can significantly decrease customer retention during the onboarding stage. Moving to leaner communication channels can aggravate such attrition. Finally, a cross-industry survey of B2B managers identifies complexity perceptions as the likely source of these detrimental effects of add-on bundling during the customer onboarding stage.
Keywords: 330; Bundling; Add-on services; Software-as-a-service; Subscription services; B2B services; Customer onboarding; Customer retention; Relationship marketing